Exploring Information Communication and Technology (ICT) Integration in English for Foreign Learners (EFL) Classroom : A Case Study at Senior High School in Kuantan Mudik Regency - Herman, Nur Ingsira Fitrah; Settiawan, Dodi; Bukhori, Bukhori (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research investigates the implementation of Information and Communication Technology (ICT) in English as a Foreign Language (EFL) classrooms through the lens of the TPACK framework. Data collection methods included analysis of lesson plans, classroom observations, and interviews with both teachers and students from two senior high schools. The findings indicate that although teachers were aware of curriculum objectives and expressed intentions to integrate ICT, its actual use was limited and inconsistent. Most applications were confined to simple PowerPoint presentations, lacking multimedia elements and interactivity. Instruction largely remained teacher-centered, with minimal student participation and limited use of collaborative or digital learning resources. Viewed through the TPACK perspective, teachers demonstrated strong content knowledge (CK) and some pedagogical knowledge (PK), but their technological knowledge (TK) was insufficient. Their integration of technology with content (TCK) and pedagogy (TPK) was shallow, and comprehensive TPACK implementation was absent. This aligns with existing literature, which often notes the difficulty educators face in effectively merging all three knowledge domains. Contributing obstacles included inadequate infrastructure, unstable internet connections, low digital confidence among teachers, and classroom management challenges when students used personal devices issues that are commonly cited in ICT integration research. Despite these challenges, both educators and learners acknowledged the potential of ICT to enhance learning by making lessons more engaging and understandable through visual and audio aids. In summary, technology use must go beyond presence it needs to be thoughtfully embedded into teaching strategies and subject content. This reinforces the core principle of TPACK: that impactful, technology-supported instruction requires a balanced integration of technological, pedagogical, and content knowledge.